Saturation effect for dependence of the electrical conductivity of planar oriented nematic liquid crystal 6CB on the concentration of Cu7PS6 nanoparticles - Kovalchuk, O. V. (2019)
The influence of Cu7PS6 nanoparticles with the average size 117 nm on the dielectric properties of planar oriented nematic liquid crystal 6CB has been investigated within the frequency range 10(1) ...10(6) Hz and at the temperature 293 K. It has been shown that when changing the concentration of nanoparticles within the range 0 to 1 wt.%, the conductivity of the liquid crystal changes stronger than its dielectric permittivity. It has been shown that the electrical conductivity increases monotonously with increasing the concentration of nanoparticles. However, for this dependence a saturation effect is observed. The mechanism of this effect was proposed.